Classifying Persuasive Strategies in Head Boy Election Speeches Using the Elaboration Likelihood Model - Amanda Maharani Sandrina; Otong Setiawan Djuharie (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This research examines the persuasive strategies used by student candidates in the 2020 Head Boy election at The Fulham Boys School in London, England. Specifically, on how teenagers convey persuasive messages in a formal school-based leadership context to persuade their peers. The study aims to identify and categorize the persuasive elements of their campaign speeches through Petty and Cacioppo's the Elaboration Likelihood Model (ELM) which differentiates between central (logical, content driven) and peripheral (emotional, stylistic) routes to persuasion. With a qualitative descriptive approach, the campaign speeches were collected in video format and transcribed, then they were content analyzed according to several categories. Each persuasive statement was classified according to the ELM principles. All four candidates were found to be applying center and peripheral routes and had responsibility of both audience demands and the leadership image. Some candidates were predisposed to use rational solutions, while others made more use on emotional appeals. This highlights the complexities involved in a student speaker's role in a leadership speech that balanced the appeal of the message against the message itself.